How does urbanization influence PM2.5 concentrations? Perspective of spillover effect of multi-dimensional urbanization impact. (20th May 2019) - Du, Yueyue; Wan, Qing; Liu, Haimeng; Liu, Hao; Kapsar, Kelly; Peng, Jian
Abstract: China's rapid urbanization has aggravated its air pollution problems and subsequently results in increased interests in the relationship between urbanization and PM2.5 concentrations. Currently, research on the ways that urbanization directly influences air quality are comparatively mature; however, quantification of the spillover effect of urbanization on PM2.5 concentrations in adjacent regions remains understudied. Additionally, urbanization is a multi-dimensional phenomena in China and it is important to distinguish the ways in which the multiple aspects of urbanization influence PM2.5 concentrations. Taking the Beijing-Tianjin-Hebei Urban agglomeration of China as an example, this study explored the spatio-temporal change and spatial dependence pattern of PM2.5 concentrations, and further examined and compared the unique impacts of the multiple dimensions of urbanization on PM2.5 concentrations. The results showed that spatial dependence of PM2.5 generally took place over the range of 200 km in the study area. Economic urbanization had a much stronger influence on air quality than land urbanization or population urbanization; it was determined to be the best indicator to represent the impact of urbanization, especially the spillover effect of urbanization on PM2.5 concentrations in adjacent regions. Over the period 2000–2010, the impacts from both local and neighboring economic urbanization on PM2.5 concentrations increased significantly. In contrast, land urbanization mainly exerted influence on air quality in focal regions. Population urbanization showed no significant direct or spillover effects on PM2.5 concentrations in the whole urban agglomeration. This study provides evidence that the influence of urbanization within and across cities must be considered when conducting joint air pollution control in an urban agglomeration. PM2.5 taxes based on the diffusion and transfer of environment pressures are one possible policy mechanism that could help to account for the spillover effect of economic urbanization on air quality. System-based approaches and flow-centered governance are two suggested ways to coordinate the management of both urbanization and air quality. Highlights: Spatial dependence of PM2.5 concentrations occurs over the range of 200 km in BTH. Spillover effect of urbanization on PM2.5 occurs through various approaches. Development of economic, land, population urbanization is inconsistent in BTH. Economic urbanization can best indicate the impact of urbanization on PM2.5 .